Upaya Meningkatkan Kemampuan Gerak Dasar Lompat melalui Modifikasi Permainan pada Materi Senam Ketangkasan pada Siswa Kelas 5c SDN Manukan Kulon Surabaya Semester Genap Tahun Pelajaran 2022/2023 - Adimas Tobi; Anung Priambodo; Rindra Putra Prasetya (Departement of Mathematics Education, 2023)
The purpose of this study was to improve the basic jumping ability of class 5C students at SDN Manukan Kulon. One indication of the lack of maximum PJOK learning can be seen from the results of the skills scores of class 5C students who are still below the Minimum Completeness Criteria, namely 85. This research uses classroom action research carried out in 2 cycles, in which there are main stages of activity, namely planning, implementing, observing and reflection. The population and research sample used 5C class students with a total of 30. The data collection method consisted of ability tests, observation, and documentation. While the research instrument used skill assessment sheets and attitude observation sheets. Analysis of skills assessment data using a collaborative approach to qualitative and quantitative descriptive methods. Based on the results of the study, judging from the scores on the pretest, there were 13 students or 43% had not completed and 17 students or 57% had completed with an average score of 83.1. There was an increase in cycle I, namely 21 students or 71% completed and 9 students or 29% incomplete, with an average score of 85.6. In cycle II, there was an increase of 26 students or 87% complete and 4 students or 13% incomplete, with an average score of 87.8. According to the classical completeness criteria, more than 80% of students complete. In conclusion, by modifying the game on agility gymnastics material can improve the basic jumping ability.